Communicational power of social networks: The critique of contemporary narcissism - Vuksanović, Divna (CM: Communication and Media, 2014)
This text draws attention to the so-called ‘dark side’ of the Internet and social media, with the special focus on popular network Facebook. Namely, in the time of escalation of new communication technologies, which again confirms the power of media, there is evidence that these technologies enable not only connection and instant interaction between users of network communication, but also a new form of social behavior – media constructed narcissism. This is not individual (Freud) or social narcissism (Lasch), but it is the case of completely new form of narcissistic behavior, that is illustrated using social network Facebook as example. Furthermore, judging by the research done among students in the USA, malignant narcissistic behavior (Vaknin), becomes new paradigm of ‘sociablity’, and, in other words, interaction. Number of friends on a certain profile verifies this sociability. Thus, this is socially constructed narcissism in cyber space, which is becoming, more and more, a trait of global culture that surrounds us.